Pengembangan Digital Flipbook Terintegrasi Mind Map (DFM) Untuk meningkatkan Pemahaman Konsep Siswa Kelas XI pada Materi Sistem Pencernaan di SMA - Fauzianti, Windi; Tambunan, Efrida Pima Sari (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop digital learning media in the form of flipbooks integrated with mind mapping to improve the understanding of concepts of grade XI students in the digestive system material at SMA Negeri 2 Percut Sei Tuan. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. At the development stage, the media was validated by material and media experts who showed results of 97.77% with the criteria of "very feasible" and 98% with the criteria of "very practical", then continued with the dissemination stage through implementation media to students. The subjects of the study consisted of biology teachers and grade XI students, with a large group sample of grade XIb and a small group of 10 students randomly. Data collection was carried out through interviews and questionnaires, while the validity of the media was measured through expert validation tests. The results of the study indicate that the digital flipbook learning media integrated with mind maps (DFM) is considered feasible and effective to use, able to improve students' understanding of complex digestive system material seen from the results of the N-Gain percentage of 0.78 indicating a "high" criterion, and significantly increase motivation and learning outcomes. This media is also considered interesting and interactive, so it can overcome students' difficulties in understanding biological concepts through structured and easy-to-understand visual presentations, and provide innovative solutions in biology learning in schools.